Exploring the possibilities with shared spreadsheets in gathering and analyzing information on the usage of study rooms in a university library - Reberg, Mikael (Qualitative and Quantitative Methods in Libraries; Vol 9 No 1 (2020): March 2020 Issue, 2020)
In autumn 2018, a team within the Mid Sweden University Library decided to advance the usage of different methods inspired by the perspectives within the field of “UX” to study the use of the learning spaces in the library. A special project concerned the students’ use of group study rooms. Here the library employed a method where student mentors working for the library gathered basic statistical data through observations. The student mentors measured the usage of the study rooms, seats used, technology used in the rooms, sound levels etcetera at several time points each day. The information was continuously registered in a shared Google sheet that also worked as the basic tool for the analysis. The results of the study gave important guidance for the development of the study rooms and the learning environment in general. More importantly, the use of Google and the shared process of collecting and analyzing information was seen as a rewarding learning experience by the student mentors and the involved library staff.